2019
DOI: 10.3390/ijms20030479
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Metabolism: New Insight into Ceramide-Induced Lipotoxicity in Muscle Cells

Abstract: Insulin-resistance is a characteristic feature of type 2 diabetes (T2D) and plays a major role in the pathogenesis of this disease. Skeletal muscles are quantitatively the biggest glucose users in response to insulin and are considered as main targets in development of insulin-resistance. It is now clear that circulating fatty acids (FA), which are highly increased in T2D, play a major role in the development of muscle insulin-resistance. In healthy individuals, excess FA are stored as lipid droplets in adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 152 publications
(245 reference statements)
2
66
0
2
Order By: Relevance
“…These lipid mediators have been associated with the activation of the inflammatory response, ROS production, mitochondrial dysfunction, autophagy deregulation, endoplasmic reticulum stress (ER stress) and apoptosis [69,80,81]. This fact is mainly due to the accumulation of intermediary toxic metabolites, such as diacylglycerol, fatty acyl-CoA, ceramides, and sphingolipids, which are involved in protein kinase C (PKC) activation, triglyceride synthesis, and mitochondrial dysfunction [82,83].…”
Section: The Fatty Kidney In Dnmentioning
confidence: 99%
“…These lipid mediators have been associated with the activation of the inflammatory response, ROS production, mitochondrial dysfunction, autophagy deregulation, endoplasmic reticulum stress (ER stress) and apoptosis [69,80,81]. This fact is mainly due to the accumulation of intermediary toxic metabolites, such as diacylglycerol, fatty acyl-CoA, ceramides, and sphingolipids, which are involved in protein kinase C (PKC) activation, triglyceride synthesis, and mitochondrial dysfunction [82,83].…”
Section: The Fatty Kidney In Dnmentioning
confidence: 99%
“…Ceramides are synthesized in all metabolic tissues in HFD-fed rodents and obese humans, and have been linked to IR as reviewed in detail in previous issues of the journal [ 16 , 47 ]. This appears to be independent of an increased dietary intake of ceramides, resulting rather from an increased cellular endogenous production either due to increased substrate availability or changes in synthesis enzymes [ 47 , 48 , 49 ].…”
Section: Causal Role Of Ceramides In Insulin Resistance?mentioning
confidence: 99%
“…This appears to be independent of an increased dietary intake of ceramides, resulting rather from an increased cellular endogenous production either due to increased substrate availability or changes in synthesis enzymes [ 47 , 48 , 49 ]. Synthesis and degradation pathways and their regulation, which govern total ceramide content, have been extensively reviewed in the past few years [ 16 , 48 , 49 ]. Ceramides are mainly produced through de novo synthesis ( Figure 1 ).…”
Section: Causal Role Of Ceramides In Insulin Resistance?mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased bioactive lipid in obesity, ceramide, contributes to insulin resistance and lipotoxicity. The quantification of plasma ceramide as a biomarker could predict major adverse cardiac events [80][81][82][83]. Zhu and colleagues showed that ASAH2 treatment might overcome palmitic acid (PA)-induced insulin resistance and also block PA-induced oxidative stress where ceramide is involved (Table 3) [84,85].…”
Section: Insulin Resistancementioning
confidence: 99%